PPP and Innovative Finance in the South African Education Sector - Mavundla, Busisiwe (Graduate School of Business (GSB), 2025)
This paper explores how innovative finance can address the financial and operational challenges faced by school feeding programmes in South Africa. Innovative finance aims to optimise social, environmental, and financial impacts using various tools, mobilising additional finance for development, and ensuring efficient use of existing funds. Scholars agree on the necessity of innovative finance to bridge the funding gap for achieving SDG 4 - Quality Education. Innovative finance can harness private sector participation to attract funds, foster innovation, and promote social justice in education. Besides attracting funds to support global development efforts, innovative finance tools in education can help reform state practices by improving education ministry operations. School feeding programmes are critical educational interventions globally, yet they face hurdles in terms of effectiveness due to operational and financial limitations. The research indicates that the key challenges experienced are related to financing. The methodology used is exploratory qualitative research through interviews, focusing on South Africa as a single case study. Interview responses from educators and the education ministry district officer in Thabo Mofutsanyana district provide a representative example of the national school feeding programme due to the standardised implementation rule of the National School Nutrition Programme. The main question addressed is how innovative finance can assist school feeding stakeholders in overcoming operational and financial challenges. Three sub-questions were identified: necessary operational modifications, considerations for selecting the ideal finance model, and how innovative finance strategies in public-private partnerships can facilitate investment into the programme. The results are presented in the form of a proposed funding model which is a modified social impact bond structure as well as key recommendations on programme design. This paper proposes using innovative finance to diversify funding, strengthen monitoring and evaluation, partner with the private sector to support expansion and sustainability, and encourage local procurement and community involvement.